2012
DOI: 10.1177/0748233712468025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical warfare on respiratory symptoms, pulmonary function tests and their reversibility 23–25 years after exposure

Abstract: Pulmonary complications due to mustard gas exposure range from no effect to severe bronchial stenosis. Pulmonary function tests (PFTs) and respiratory symptoms in chemical war victims were studied 23-25 years after exposure to sulfur mustard (SM). Respiratory symptoms were evaluated in a sample of 142 chemical war victims and 120 control subjects with similar age from the general population using a questionnaire including questions on respiratory symptoms in the past year. PFT values were also measured in chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results of previous studies showed that SM exposure led to chronic bronchitis, pulmonary fibrosis and bronchiectasis in 197 veterans, 10 years after exposure, 43,44 and reduction in PFT values and increased respiratory symptoms 23-25 years after exposure. 45 Furthermore, the relaxant effect of CAR on the tracheal smooth muscle of guinea pigs 46,47 and its inhibitory effect on muscarinic 17 and histamine H 1 receptors 16 as well as its stimulatory effect on β2-adrenoreceptors in tracheal smooth muscle were shown. 48 The relaxant effect of CAR on airway smooth muscle (bronchodilatory effect) supports the results of the present study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of previous studies showed that SM exposure led to chronic bronchitis, pulmonary fibrosis and bronchiectasis in 197 veterans, 10 years after exposure, 43,44 and reduction in PFT values and increased respiratory symptoms 23-25 years after exposure. 45 Furthermore, the relaxant effect of CAR on the tracheal smooth muscle of guinea pigs 46,47 and its inhibitory effect on muscarinic 17 and histamine H 1 receptors 16 as well as its stimulatory effect on β2-adrenoreceptors in tracheal smooth muscle were shown. 48 The relaxant effect of CAR on airway smooth muscle (bronchodilatory effect) supports the results of the present study.…”
Section: Discussionmentioning
confidence: 94%
“…The results of previous studies showed that SM exposure led to chronic bronchitis, pulmonary fibrosis and bronchiectasis in 197 veterans, 10 years after exposure, and reduction in PFT values and increased respiratory symptoms 23‐25 years after exposure …”
Section: Resultsmentioning
confidence: 99%
“…All of these compounds have shown improvement in SM-and CEESinduced lung injury. [48][49][50][51] These results indicate not only the complex toxic mechanisms of action of these vesicating agents but also the need for future research in this area in order to identify more selective anti-inflammatory agents as well as possible combinations of pharmacologic antagonists targeting other affected pathways.…”
Section: Anti-inflammatory Drugmentioning
confidence: 99%
“…Epithelial damage of the airways has also been reported in chemical warfare victims (Bahadori et al, 1989; Emad et al, 1995). Reduction of pulmonary function (Boskabady et al, 2015) and increase in airway responsiveness to methacholine (Mirsadraee et al, 2005) and salbutamol (Boskabady et al, 2008) following exposure to SM were also shown. Treatments suggested for respiratory disorders caused by SM are sodium thiosulfate, cysteine, dexamethasone, and vitamin E (Hosseini et al, 1989; Somani and Babu, 1989).…”
Section: Introductionmentioning
confidence: 99%